Democratic decentralization in the forestry sector: lessons learned from Africa, Asia and Latin America - Larson, A.M. (Earthscan, 2005)
Local governments are increasingly important actors in forest management. Looking at roughly 20 countries in Africa, Asia and Latin America, this paper identifies common patterns and extracts lessons that will allow us to better understand decentralization successes and failures. It begins by brief discussion on conceptual issues that shape our understanding of decentralization in theory and practice. The next section presents the lessons learned regarding legal and institutional frameworks; financial management; the role of central governments; the role of third-party actors such as donors and non-governmental organizations (NGO); local peoples; local governments; the timber industry; other factors affecting forestry decentralizations; and outcomes. The final section makes some suggestions for the future.